1994
DOI: 10.2135/cropsci1994.0011183x003400030010x
|View full text |Cite
|
Sign up to set email alerts
|

Russian Wheat Aphid Resistance in Barley: Inheritance and Linked Molecular Markers

Abstract: Russian wheat aphid (RWA), Diuraphis noxia (Mordvilko), is an important pest of small grains cereals in many areas throughout the world. This research was conducted to determine the inheritance of resistance and to identify molecular markers of resistance in the barley (Hordeum vulgare L.) lines PI366444 and PI366453. Artificial infestation was performed in the field and growth chamber. Sodium dodecyl sulphate‐polyacrylamide gel electrophoresis, Southern blotting, and polymerase chain reaction (PCR) techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…In cereal crops, genes from barley, Hordeum vulgare L., rye, Secale cereale L., or wheat, Triticum aestivum L., confer resistance to the Russian wheat aphid, Diuraphis noxia (Mordvilko) (Smith et al., 1999) and the greenbug, Schizaphis graminum (Rondani) (Teetes et al., 1999). Results with wheat (Liu et al., 2001, 2002, 2005) and barley (Nieto‐Lopez & Blake, 1994; Moharramipour et al., 1997) indicate that aphid resistance R gene loci are located on Triticeae homoeologous groups 1 and 7.…”
Section: Introductionmentioning
confidence: 99%
“…In cereal crops, genes from barley, Hordeum vulgare L., rye, Secale cereale L., or wheat, Triticum aestivum L., confer resistance to the Russian wheat aphid, Diuraphis noxia (Mordvilko) (Smith et al., 1999) and the greenbug, Schizaphis graminum (Rondani) (Teetes et al., 1999). Results with wheat (Liu et al., 2001, 2002, 2005) and barley (Nieto‐Lopez & Blake, 1994; Moharramipour et al., 1997) indicate that aphid resistance R gene loci are located on Triticeae homoeologous groups 1 and 7.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers associated with major insect resistance genes were reported in tomato (Maliepaard et al 1995;Mutschler et al 1996), wheat (NietoLopez andBlake 1994;Dweikat et al 1997), rice (Ishii et al 1994;Nair et al 1996), corn (Byrne et al 1996(Byrne et al , 1997, mungbean (Young et al 1992), potato (Bonierbale et al 1994;Yencho et al 1996) and soybean (Hammond et al 2001). Quantitative resistance to insect pests was found in soybean for traits like antixenosis, antibiosis and pubescence shape (Terry et al 2000;Narvel et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Further study indicated that the two CIMMYT lines, derived from the crosses Gloria/Come and ASE/2CM//B76BB, contained the same dominant gene . An additional QTL on 2H (Rdn3) was present in STARS9301B and in its resistant parent accession, and chlorosis ratings on STARS9301B are consistently one point lower than those of STARS9577B (Mittal et al, 2008(Mittal et al, , 2009Nieto-Lopez and Blake, 1994;Raman and Read, 2000). The RWA biotype USA1 has been used to examine the genetics of resistance in the first two lines extensively used to develop RWA resistant germplasm, STARS9301B and STARS9577B.…”
mentioning
confidence: 99%